Observation of structural, mechanical, thermal and microwave dielectric properties of carbon black reinforced PA6/HDPE nanocomposites - Wang, Yue; Niu, Zhipeng; Han, Haorui; Wang, Jie; Lan, Di (Journal of materials science. Materials in electronics, 2023)
Nylon 6 (PA6) has been widely used in the field of specialty engineering plastics due to its excellent mechanical properties and thermal stability. However, the high water absorption rate of pure PA6 limits its suitability for more complex and demanding environments. In this study, PA6/high-density polyethylene (HDPE)/carbon black (CB) composites were prepared to investigate the effects of different CB contents on the mechanical properties, thermodynamic properties, and transparency of the PA6/PE composites. The results showed that when the CB content reached 4.5%, the composite material exhibited improved tensile strength and impact strength, reaching 53.3 MPa and 13.2 J/m 2 , respectively. The uniform dispersion of CB within the matrix contributed to more even stress distribution in the composite material and absorbed part of the impact force, and both melting peaks shift towards the left to some extent. Furthermore, the overall real part of the dielectric constant is about 2.5, and dielectric loss tangent of the material reached an extremely low level below 0.01 under this filling ratio. The island-like structure of HDPE and the dispersed CB particles embedded in it exhibited isotropic crystal symmetry. This structure is similar to an isotropic antenna and may play an important role in the transmission of electromagnetic waves. The enhanced comprehensive properties make this PA6-based composite material highly promising in the field of wideband transmission materials.